The English Language Teachers’ Perspective of Using the First Language (L1) in Teaching a Foreign Language (TEFL) Class - Yella Dezas Perdani (Bina Nusantara University, 2021)
The research discussed the using of the first language in teaching a foreign language that had been a debate for language teaching practitioners for decades in language acquisition. The debate was about whether it was all right to use it in a foreign language class or not and how it affected the students’ learning process and result. Because of the pro and cons of using the first language (L1) in teaching a foreign language, the research was conducted to find out the use of the first language in teaching English as a foreign language. The research aimed to discover to what extent and in which instances L1 was used by the teachers in their English teaching class in terms of the teaching stages, including pre-teaching, whilst-teaching, and post-teaching in the classroom. The research also searched teachers’ perspectives and reasons for using L1 in their English class. Moreover, the research applied a qualitative method to gather information from the participants. The participants were four English teachers who taught English at senior high school in Bandung-West Java province, Majalengka-West Java province, Pangkal Pinang-Bangka Province, and Kuok-Riau Province. Data collkection was done by distributing questionnaires and doing interviews. The findings show that most teachers use Indonesian as L1 in the whilst-teaching stage when they deliver the materials. They use L1 to clarify the students’ understanding of the materials given and explain English language concepts, grammatical concepts, and difficult words. They argue that using L1 helps both teachers and students in teaching and learning English as a foreign language.